Anticancer drugs in Portuguese surface waters – Estimation of concentrations and identification of potentially priority drugs. (October 2017) - Santos, Mónica S.F.; Franquet-Griell, Helena; Lacorte, Silvia; Madeira, Luis M.; Alves, Arminda
Abstract: Anticancer drugs, used in chemotherapy, have emerged as new water contaminants due to their increasing consumption trends and poor elimination efficiency in conventional water treatment processes. As a result, anticancer drugs have been reported in surface and even drinking waters, posing the environment and human health at risk. However, the occurrence and distribution of anticancer drugs depend on the area studied and the hydrological dynamics, which determine the risk towards the environment. The main objective of the present study was to evaluate the risk of anticancer drugs in Portugal. This work includes an extensive analysis of the consumption trends of 171 anticancer drugs, sold or dispensed in Portugal between 2007 and 2015. The consumption data was processed aiming at the estimation of predicted environmental loads of anticancer drugs and 11 compounds were identified as potentially priority drugs based on an exposure-based approach ( PEC b > 10 ng L −1 and/or PEC c > 1 ng L −1 ). In a national perspective, mycophenolic acid and mycophenolate mofetil are suspected to pose high risk to aquatic biota. Moderate and low risk was also associated to cyclophosphamide and bicalutamide exposition, respectively. Although no evidences of risk exist yet for the other anticancer drugs, concerns may be associated with long term effects. Graphical abstract: Highlights: 11 anticancer drugs were identified based on an exposure criteria. Mycophenolic acid and mycophenolate mofetil represent high risk to aquatic life. Moderate risk was associated to cyclophosphamide exposition. Bicalutamide is suspected to pose low risk to aquatic biota.